Kazys Boruta in the Soviet Security Surveillance Case - Daugėlaitė, Brigita (Colloquia, 2024)
The article examines the operational surveillance case of Kazys Boruta (1905-1965), until now not extensively researched material, collected by the Soviet security from 1945 until writer’s death and the actions taken by the security services against him. The aim of this article is to investigate the reasons behind the surveillance of Boruta that lasted for twenty years and to reveal in more detail the influence of the Soviet authorities on writer’s life and work. Boruta’s views during the Soviet era and some of his contacts during the occupation could not be freely discussed. Using the currently available security information, the article scrutinizes how the various suspicions against Boruta were tailored and, in turn, what reactions of the security services were triggered. It discusses the investigation into Boruta’s alleged activities in underground organizations: his links with the Lithuanian National Council and the Lithuanian partisan movement, as well as the relations and activities of the SRs who were active between the wars and during the Soviet period. The article also discusses the significance of Boruta’s anti-Soviet and nationalist statements in the surveillance process and the attitude of the security services towards his work that did not meet ideological requirements of the time.